Le docufiction l’Odyssée de l’espèce. Analyse didactique et pistes d’exploitation en classe de terminale S - Yannick Rech; Eric Triquet (Revue de Primatologie)
The evolution of the human lineage is a strong theme of French programs in Life sciences at the college and high school. It is also at the heart of television fictional documentary reporting a narrative scenography. The sake of realism rivals here with imaginary fiction. Although renowned anthropologists have given their guarantee to scenarios, these general public films show evidence for a certain distancing to scientific data. Rather than ignoring these media, whose popularity among young’s has surprised many researchers and broadcasters of the major TV channels, it is of particular interest to present them to students in a critical perspective. In this article, we present the analysis of the movie the “Odyssey of the species" produced by Jacques Malaterre and suggestions to study it with pupils of the end of high school.